Extracting multiple interacting root systems using X-ray micro computed tomography - Mairhofer, Stefan; Sturrock, Craig; Bennett, Malcolm J.; Mooney, Sacha J.; Pridmore, Tony P. (Wiley, 2015)
Root system interaction and competition for resources is an active research area that contributes to our understanding of roots’ perception and reaction to environmental conditions. Recent research has shown this complex suite of processes can now be observed in a natural environment (i.e. soil) through the use of X-ray micro Computed Tomography (µCT), which allows non-destructive analysis of plant root systems. Due to their similar X-ray attenuation coefficients and densities, the roots of different plants appear as similar greyscale intensity values in µCT image data. Unless they are manually and carefully traced, it has previously not been possible to automatically label and separate different root systems grown in the same soil environment. We present a technique, based on a visual tracking approach, which exploits knowledge of the shape of root cross-sections to automatically recover 3D descriptions of multiple, interacting root architectures growing in soil from X-ray µCT data. The method was evaluated on both simulated root data and real images of two interacting winter wheat Cordiale (Triticumaestivum L.) plants grown in a single soil column, demonstrating that it is possible to automatically segment different root systems from within the same soil sample. This work supports the automatic exploration of supportive and competitive foraging behaviour of plant root systems in natural soil environments.